2022
DOI: 10.1186/s13287-022-03020-w
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming adipose mesenchymal stem cells into islet β-cells for the treatment of canine diabetes mellitus

Abstract: Background Islet transplantation is an excellent method for the treatment of type I diabetes mellitus. However, due to the limited number of donors, cumbersome isolation and purification procedures, and immune rejection, the clinical application is greatly limited. The development of a simple and efficient new method to obtain islet β-cells is a key problem that urgently requires a solution for the treatment of type I diabetes mellitus. Methods In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…For example, FTO expression is increased in NAFLD, and it promotes hepatic steatosis by targeting PPARa (61). Its upregulation can reduce insulin secretion via the inflammatory NF-kB pathway and disrupts lipid utilization in skeletal muscles by suppressing the PPARb/dand AMPK pathways, leading to the occurrence of diabetic hyperlipidemia (62).A recently research found that RFX3 is a novel functional genes that regulate the development of adipose mesenchymal stem cells into islet b-cells (63). KSR2 plays an important role in energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, FTO expression is increased in NAFLD, and it promotes hepatic steatosis by targeting PPARa (61). Its upregulation can reduce insulin secretion via the inflammatory NF-kB pathway and disrupts lipid utilization in skeletal muscles by suppressing the PPARb/dand AMPK pathways, leading to the occurrence of diabetic hyperlipidemia (62).A recently research found that RFX3 is a novel functional genes that regulate the development of adipose mesenchymal stem cells into islet b-cells (63). KSR2 plays an important role in energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The lab preserved frozen P3 generation cADMSCs were resuscitated using FBS medium. The isolation, culture and identification of the cells are shown in the previous results [ 14 , 15 ], and after the cells were attached to the wall, the medium was abandoned, and the cells were cultured through the above medium, respectively, to observe the growth rate and growth morphology of the cells. At the same time, cells were tested for proliferation according to the instructions of Cell Counting Kit-8 (Sigma‒Aldrich, 96992-500TESTS-F, USA).…”
Section: Methodsmentioning
confidence: 99%
“…MSCs restore mucosal immunity and rejuvenate mucosal immunosenescence in the elderly [ 22 ]. Moreover, reprogramming AMSCs into islet β-cells (reprogrammed AMSCs-derived islet β-cells) with low immunogenicity achieved ideal therapeutic effects in treating canine diabetes mellitus [ 23 ].…”
Section: Introductionmentioning
confidence: 99%